2020
DOI: 10.1002/jmv.26266
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of memantine use and COVID‐19‐associated mortality from a national database

Abstract: who are at higher risk of COVID-19, and, therefore, ideal candidates for retrospective investigations aimed at determining whether memantine has therapeutic effects on COVID-19. In conclusion, our analysis revealed no association between memantine treatment and mortality in patients with COVID-19. However, we must explore all feasible options for preventing and treating COVID-19 due to the current lack of licensed vaccines or therapeutics for the disease. A low-risk and cost-effective strategy could be trial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…following documented exposure but none of them went on to develop clinical manifestations of infectious disease [43]. Similar findings were subsequently independently reported in a patient with type-2 diabetes and members of his immediate family all of whom tested positive for COVID-19 and were being treated with amantadine as well as in a further case of an amantadine-treated patient with Parkinson's disease [44,45]. In a related study, treatment with memantine [10 mg bid] was reported to manifest apparently protective effects in a group of 7 patients with cognitive impairment who tested positive for COVID-19 [42].…”
Section: Memantine or Amantadine For Prevention Of Covid-19: Clinicalsupporting
confidence: 69%
See 2 more Smart Citations
“…following documented exposure but none of them went on to develop clinical manifestations of infectious disease [43]. Similar findings were subsequently independently reported in a patient with type-2 diabetes and members of his immediate family all of whom tested positive for COVID-19 and were being treated with amantadine as well as in a further case of an amantadine-treated patient with Parkinson's disease [44,45]. In a related study, treatment with memantine [10 mg bid] was reported to manifest apparently protective effects in a group of 7 patients with cognitive impairment who tested positive for COVID-19 [42].…”
Section: Memantine or Amantadine For Prevention Of Covid-19: Clinicalsupporting
confidence: 69%
“…A retrospective study of a national database of 5726 patients, 140 of whom subsequently died, did not reveal any statistical difference in mortality of a group of patients between COVID-19 associated mortality and ongoing treatment with memantine for dementia, indicating it's not likely to have therapeutic effects on patients with COVID-19, however it did not seem to have any deleterious effects [45].…”
Section: Memantine or Amantadine For Prevention Of Covid-19: Clinicalmentioning
confidence: 96%
See 1 more Smart Citation
“…A few case reports suggest a possible beneficial effect of amantadine on the clinical course of COVID-19 53 . An observational study using a national Korean database found no effect of memantine on the course of COVID-19 disease 54 . Further clinical data for either drug in COVID-19 patients is not available.…”
Section: Other Neuropsychiatric Drugsmentioning
confidence: 98%